Manajemen Retribusi Parkir Di Pasar Inpres Kota Palu - Yuliastono, Muh. Fendy; Suasa; Mukarramah (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This study was motivated by the suboptimal management of parking retribution at Inpres Market in Palu City, which has resulted in revenue leakage and weak supervision of parking attendants. The objective of this research is to describe the management of parking retribution at Inpres Market based on the management functions proposed by Henry Fayol, namely planning, organizing, commanding, coordinating, and controlling. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation involving the Palu City Department of Transportation, parking attendants, traders, and service users. The findings show that, in terms of planning, revenue targets and official parking tickets have been established; however, their implementation remains ineffective, as many users do not receive official tickets. In terms of organizing, task distribution has been arranged, yet overlapping duties and an unclear work structure are still found. The directing aspect has not been carried out consistently, as guidance and supervision for attendants remain limited. Coordination among related stakeholders has not been optimal, while controlling mechanisms are still weak, resulting in potential revenue leakage. Overall, the management of parking retribution at Inpres Market has been implemented, but it has not been effective, thus requiring stronger supervision and the application of a digital-based payment system to improve transparency and increase local revenue.